The NOHS 2024 Code of Ethics Update - Kevin C Snow; Christian Williams; Ed Neukrug; Kristin Barker; Kristin Ballard; Braxton A Morrison; Leslie C.M. McClane; Meghan N. Morgan; Stephanie Collins (Journal of Human Services)
The NOHS Ethics committee engaged in a revision of the Ethical Standards for Human Services Professionals (2024). This update focused on significant changes in the field of human services as they relate to a broad group of human services professionals. The article explores interviews with key members of the revision committee sharing their thoughts on the necessity for the current revision and the ever-present importance for human service professionals to understand and engage with the NOHS ethics code as an essential living document for the benefit of client well-being, to promote the integrity of the human services profession, and to support professional relationships that are respectful and trustworthy within the wide diversity of human services stakeholders (e.g., practitioners, students, faculty, administrators, leaders).